A Quiet Revolution in Corporate Governance: An Examination of Voluntary Best Practice Governance Policies. (13th November 2013) - Baulkaran, Vishaal
Abstract This paper investigates the effects of several voluntary best practice corporate governance principles on firm performance and firm risk. Using a sample of Standard & Poor's/Toronto Stock Exchange Composite Index firms from 2003–2010, I show that firms with individual director election and detailed disclosure of voting results in director elections have a higher firm value or performance. Firms with independent chairman, majority voting, and detailed disclosure of voting results in director elections have lower idiosyncratic risk. In addition, the results from the panel regression show that detailed disclosure of voting results in director election leads to lower systematic and total risk.